Answer:
C. ![f(x)=\frac{x+1}{x-1}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7Bx%2B1%7D%7Bx-1%7D)
Step-by-step explanation:
Let's find the inverse of each of the given options.
Option A:
![f(x)=\frac{x+6}{x-6}\\y=\frac{x+6}{x-6}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7Bx%2B6%7D%7Bx-6%7D%5C%5Cy%3D%5Cfrac%7Bx%2B6%7D%7Bx-6%7D)
To find
, replace 'x' with 'y' and 'y' with 'x'. This gives,
![x=\frac{y+6}{y-6}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7By%2B6%7D%7By-6%7D)
Rewrite in terms of 'y'. This gives,
![x(y-6)=y+6\\xy-6x=y+6\\xy-y=6x+6\\y=\frac{6x+6}{x-1}](https://tex.z-dn.net/?f=x%28y-6%29%3Dy%2B6%5C%5Cxy-6x%3Dy%2B6%5C%5Cxy-y%3D6x%2B6%5C%5Cy%3D%5Cfrac%7B6x%2B6%7D%7Bx-1%7D)
The given function ![y=\frac{6x+6}{x-1}\ne y=\frac{x+6}{x-6}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B6x%2B6%7D%7Bx-1%7D%5Cne%20y%3D%5Cfrac%7Bx%2B6%7D%7Bx-6%7D)
So, option A is incorrect.
Option B:
![f(x)=\frac{x+2}{x-2}\\y=\frac{x+2}{x-2}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7Bx%2B2%7D%7Bx-2%7D%5C%5Cy%3D%5Cfrac%7Bx%2B2%7D%7Bx-2%7D)
To find
, replace 'x' with 'y' and 'y' with 'x'. This gives,
![x=\frac{y+2}{y-2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7By%2B2%7D%7By-2%7D)
Rewrite in terms of 'y'. This gives,
![x(y-2)=y+2\\xy-2x=y+2\\xy-y=2x+2\\y=\frac{2x+2}{x-1}](https://tex.z-dn.net/?f=x%28y-2%29%3Dy%2B2%5C%5Cxy-2x%3Dy%2B2%5C%5Cxy-y%3D2x%2B2%5C%5Cy%3D%5Cfrac%7B2x%2B2%7D%7Bx-1%7D)
The given function ![y=\frac{2x+2}{x-1}\ne y=\frac{x+2}{x-2}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2x%2B2%7D%7Bx-1%7D%5Cne%20y%3D%5Cfrac%7Bx%2B2%7D%7Bx-2%7D)
So, option B is incorrect.
Option C:
![f(x)=\frac{x+1}{x-1}\\y=\frac{x+1}{x-1}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7Bx%2B1%7D%7Bx-1%7D%5C%5Cy%3D%5Cfrac%7Bx%2B1%7D%7Bx-1%7D)
To find
, replace 'x' with 'y' and 'y' with 'x'. This gives,
![x=\frac{y+1}{y-1}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7By%2B1%7D%7By-1%7D)
Rewrite in terms of 'y'. This gives,
![x(y-1)=y+1\\xy-x=y+1\\xy-y=x+1\\y=\frac{x+1}{x-1}](https://tex.z-dn.net/?f=x%28y-1%29%3Dy%2B1%5C%5Cxy-x%3Dy%2B1%5C%5Cxy-y%3Dx%2B1%5C%5Cy%3D%5Cfrac%7Bx%2B1%7D%7Bx-1%7D)
The given function ![y=\frac{x+1}{x-1}\ equals\ y=\frac{x+1}{x-1}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7Bx%2B1%7D%7Bx-1%7D%5C%20equals%5C%20y%3D%5Cfrac%7Bx%2B1%7D%7Bx-1%7D)
So, option C is correct.
Option D:
![f(x)=\frac{x+5}{x-5}\\y=\frac{x+5}{x-5}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7Bx%2B5%7D%7Bx-5%7D%5C%5Cy%3D%5Cfrac%7Bx%2B5%7D%7Bx-5%7D)
To find
, replace 'x' with 'y' and 'y' with 'x'. This gives,
![x=\frac{y+5}{y-5}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7By%2B5%7D%7By-5%7D)
Rewrite in terms of 'y'. This gives,
![x(y-5)=y+5\\xy-5x=y+5\\xy-y=5x+5\\y=\frac{5x+5}{x-1}](https://tex.z-dn.net/?f=x%28y-5%29%3Dy%2B5%5C%5Cxy-5x%3Dy%2B5%5C%5Cxy-y%3D5x%2B5%5C%5Cy%3D%5Cfrac%7B5x%2B5%7D%7Bx-1%7D)
The given function ![y=\frac{5x+5}{x-1}\ne y=\frac{x+6}{x-6}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B5x%2B5%7D%7Bx-1%7D%5Cne%20y%3D%5Cfrac%7Bx%2B6%7D%7Bx-6%7D)
So, option D is incorrect.
Therefore, only option C is correct.